Atrial fibrillation in breast cancer therapy: does tamoxifen confer a lower risk than aromatase inhibitors? - Patrick A. Kwaah; Samuel A. Mensah; Emmanuel A. Agyemang; Joseph S. Kekrebesi; Daniil Katkov; Abraham Carboo; Grace Appah; Hamza A. Rashid; Jennifer M. Kwan (Cardio-Oncology)
Abstract Introduction Aromatase inhibitors (AIs) have been linked to increased atrial fibrillation(AF) risk due to estrogen depletion however tamoxifen's effect on AF remains conflicting. This study investigates the risk of AF associated with AI use compared to tamoxifen in breast cancer patients. Methods A retrospective cohort analysis was conducted using the TriNetX database from 2015 to 2024. Breast cancer patients were categorized into two groups: AI users (anastrozole, exemestane, or letrozole) and tamoxifen users. A propensity score matching (1:1) adjusted for demographics, comorbidities, concurrent therapies, and lab values. The incidence of AF was assessed at 1, 5, and 10-years post-treatment initiation. Results The study included 220,552 AI users and 73,388 tamoxifen users before matching, with 54,175 patients in each group after matching. At 1 year, AI users had a higher risk of AF (0.5% vs. 0.4%, RR: 1.36, p = 0.001). At 5 years, AF incidence remained higher in the AI group (1.2% vs. 1.1%, RR: 1.13, p = 0.035).However at 10 years, the difference in AF risk between the two groups was no longer significant (1.6% vs. 1.5%, RR: 1.05, p = 0.295). Conclusion AI use is associated with a higher risk of AF than tamoxifen in the first 5 years of treatment, but the risk equalizes at 10 years. Long-term hormonal therapy has an increased risk of AF, highlighting the need for ongoing monitoring and management of risk factors.